Professional Experiences, Leadership Growth, and Progression Approaches Adopted by Women Working Within Professional Sports Organisations in Ghana - Abena Adasa Nkrumah; Daniel Apaak; Stephen Kyenkyehene Addae (Baltic Journal of Sport and Health Sciences)
The study explored experiences, leadership growth, and progression approaches adopted by women working within higher professional sports leadership organisations in Ghana. An interpretive research paradigm was adopted. The data was collected using interview guides and analysed with the Interpretative Phenomenological Analysis (IPA). The study revealed interest in a particular sport propelled women in sports leadership positions to select sports-related careers and accumulate the best knowledge and experience that placed them in such advantageous positions to make meaningful contributions to sports in Ghana. The study established that women with clear-cut career advancement pathways have it easy when it comes to assuming leadership positions. It was recommended that qualitative and quantitative examinations be made to understand the differences in the experiences of males in similar sporting positions.